Effectiveness of Warm Water Immersion Combination of Rose and Lavender Aromatherapy on Anxiety and Pain Scale of Laboring Mother in Independent Midwifery Practice - Eva Susanti; Lydia Febrina; Indah Fitri Andini (Jurnal Penelitian Pendidikan IPA, 2025)
Labor is a physiological event that occurs in the life cycle of women, in this process contractions occur which cause discomfort in the form of anxiety and pain and are correlated with each other during labor. Objective: This study was conducted to determine the effectiveness of warm water immersion on anxiety and childbirth pain scale in Independent Midwifery Practice. Methods: This study included quantitative research with quasi-experimental research with pre and post test design of control group. The sample consisted normal laboring mothers with a simple random sampling method involving 35 people in each group. Data collection employed questionnaires and observation sheets. The research was conducted from January to October 2024. Results: Based on the results of statistical tests on the research group, the results of the posttest value of fetal heart rate, contraction duration, anxiety, and pain scale obtained p-value <0.05. Conclusion: There is an effectiveness of warm water immersion with a combination of rose and lavender aromatherapy on anxiety and childbirth pain scale.